Pendampingan Pendalaman Apersepsi Siswa Pada Mata Pelajaran Agama Islam di SMP IT Subulul Huda - Herlina Zuhfatul Muniroh; Ilham Ali Asifudin; Ilham Al Akbar; Ilham Maulana Annafi'i; Irfan Ardiansyah; Muhammad 'Abdurrofi'; Nurul Malikah (https://ejournal.insuriponorogo.ac.id/, 2024)
Islamic Religious Education (PAI) is a very important subject in shaping students' character and morals. However, in the PAI learning process, obstacles are often encountered such as lack of student motivation and interest. Therefore, this research aims to identify the role of apperception in increasing students' motivation and interest in the learning process. Apperception is an effective learning method for increasing students' motivation and concentration. This article aims to increase the effectiveness of teaching and provide a positive impact on educational development and the importance of guidance as a way to improve the quality of PAI learning, especially in the apperception aspect at SMP IT Subulul Huda. The research in this article uses qualitative research methods with collection techniques data through observation and interviews. The research results show that apperception can build students' understanding, connect new material with previous knowledge, and create a conducive learning atmosphere. However, the implementation of apperception is often hampered by factors such as lack of time allocation, large amount of material, and lack of teacher competence. Thus, this research concludes that apperception is an effective strategy in increasing students' motivation and interest in the PAI learning process. and educators also need to improve their competence and optimize the use of time to achieve effective learning goals.